THE EFFECT OF AUDITOR CHARACTERISTICS ON ALLEGED FRAUD OCCURRENCE AND ITS IMPACT ON FINANCIAL STATEMENT FRAUD RISK ASSESSMENT AND AUDIT PROGRAM MODIFICATIONS - Shlof, Mohamed A. (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The goal of this study is to examine the relationships between the auditor's qualities and alleged fraudulent activity, as well as those between alleged fraudulent activity and fraud risk assessment and between fraud risk assessment and audit program modifications. The population in this study were auditors at Public Accounting Officer. Selection of samples in this population using purposive sampling method. The sample used in this study were auditors who worked at Public Accounting Officer. The analytical tool used in this study is Structural Equation Modelling which is run through the Partial Least Squares Structural Equation Modelling program. The results of the analysis in this study are the characteristics of the auditors that affect the alleged occurrence of fraud. This shows that the better the level of specialization of the auditor, the easier it will be for the auditor to detect earnings manipulation and misstatements in a company's financial statements. Fraud affects the initial fraud risk assessment. The existence of suspected fraud in the financial statements may affect the initial fraud risk assessment. If the allegations are true, the company is proven to have committed fraud. The initial fraud risk assessment has an effect on the modification of the audit program.